2023
DOI: 10.1111/jcmm.18037
|View full text |Cite
|
Sign up to set email alerts
|

ER‐α36 is involved in calycosin inhibition of IL‐6 production in macrophages

Guoli Wu,
Guangying Qi,
Yu Liu
et al.

Abstract: The tumour microenvironment (TME) is crucial for tumour development and progression. Tumour‐associated macrophages (TAMs) in the TME can promote tumour progression and metastasis by releasing cytokines, such as IL‐6. Calycosin, a phytoestrogen that is one of the active compounds in Radix Astragali, has been shown to inhibit tumour growth and metastasis. However, the underlying mechanism by which calycosin inhibits tumour growth remains unclear. Thus, this study aimed to investigate the effect of calycosin on I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…39 59 Calycosin promoted the expression of ER-α36, which is the main oestrogen receptor of ESR1, in macrophages. 60 Kaempferol notably promoted ESR1 expression in the ovaries tissue of rats with premature ovarian failure. 61 In HUVECs, MCF-7 and BT474 cells, Formononetin markedly up-regulated ESR1 expression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…39 59 Calycosin promoted the expression of ER-α36, which is the main oestrogen receptor of ESR1, in macrophages. 60 Kaempferol notably promoted ESR1 expression in the ovaries tissue of rats with premature ovarian failure. 61 In HUVECs, MCF-7 and BT474 cells, Formononetin markedly up-regulated ESR1 expression.…”
Section: Discussionmentioning
confidence: 94%
“…demonstrated that Quercetin significantly increased the expression of ESR1 in HT‐29 colon cancer cells 59 . Calycosin promoted the expression of ER‐α36, which is the main oestrogen receptor of ESR1, in macrophages 60 . Kaempferol notably promoted ESR1 expression in the ovaries tissue of rats with premature ovarian failure 61 .…”
Section: Discussionmentioning
confidence: 99%